WITHER BEFORE BLOSSOM: FETAL DEATH – A 5 YEAR RETROSPECTIVE STUDY (Journal of Forensic Medicine & Toxicology, 2024)
Fetal death remains a significant and understudied problem. Fetal autopsy and placental examination offer much valuable information for the formulation of cause of death. The present study was undertaken with an aim to provide data regarding the cause and circumstances of fetal death and to provide autopsy findings in these deaths. The retrospective study was carried out through 2004 to 2008. All cases listed as fetal death or stillbirths were included. The male: female ratio was 1: 1.2 and their age ranged from 16 weeks to full term. Most fetuses (26, 76.47%) were older than 28 weeks. The majority (25 fetuses, 73.52%) was externally normal, apart from decomposition and maceration and only 2 (5.88%) had exhibited gross congenital anomaly. Considering the manner of death, 70.58% were natural, 14.70% homicidal and 14.70% were undetermined.
Keywords: Fetus; Autopsy; Death; Stillbirth